Navigating the Moral Realm of Counseling: Counselor's Expressed Role Within and Awareness of Value Conversion. (April 2019) - Bridges, James G.; Hicks, Amelia; Lazzo, Peyton; Keegan, Sarah
This article builds off previous literature addressing the phenomenon of value conversion. We explored how aware counselors were of this phenomenon, what they did about it if they were, and how explicit they made the potential of value conversion to their clients. A total of 10 mental health counselors were interviewed from local community mental health clinics and group practices in a Midwestern city. Counselors identified which personal moral values influenced the bulk of their counseling practice. Based on various levels of uncertainty, we concluded that training discussions and clinical considerations of value conversion seldom take place. Counselors may benefit from interdisciplinary involvement from philosophical frameworks of moral theory. Future directions, limitations, and clinical implications are discussed.